2016
DOI: 10.1111/imm.12604
|View full text |Cite
|
Sign up to set email alerts
|

SHARPIN controls the development of regulatory T cells

Abstract: SummarySHARPIN is an essential component of the linear ubiquitin chain assembly complex (LUBAC) complex that controls signalling pathways of various receptors, including the tumour necrosis factor receptor (TNFR), Toll-like receptor (TLR) and antigen receptor, in part by synthesis of linear, nondegrading ubiquitin chains. Consistent with SHARPIN's function in different receptor pathways, the phenotype of SHARPIN-deficient mice is complex, including the development of inflammatory systemic and skin diseases, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 51 publications
2
15
0
Order By: Relevance
“…1a–d). Consistent with recent reports2526, we observed that Treg cells were reduced in Sharpin cpdm mice, although to a much lesser extent compared with the Hoip ΔCd4 and Hoil ΔCd4 mice (Fig. 1a,b).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…1a–d). Consistent with recent reports2526, we observed that Treg cells were reduced in Sharpin cpdm mice, although to a much lesser extent compared with the Hoip ΔCd4 and Hoil ΔCd4 mice (Fig. 1a,b).…”
Section: Resultssupporting
confidence: 93%
“…36) and our data showing that constitutive active IKK2 cannot restore peripheral T cells suggest that there are other LUBAC-dependent signals downstream of the TCR that are required for SP thymocyte maturation. Indeed, a role for SHARPIN has been implicated in JNK and ERK activation downstream of TCR signals2526. Another possibility is that LUBAC is required to transduce signals from other cell surface receptors critical for SP maturation, such as members of the TNFR superfamily.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies from two different groups have demonstrated T-cell intrinsic roles for SHARPIN, revealing a requirement for SHARPIN in regulatory T-cell development and function1920. Herein, our studies demonstrate that immune cell dysregulation precedes the development of dermatitis in Sharpin cpdm mice.…”
Section: Discussionsupporting
confidence: 51%
“…We and others showed that LUBAC plays a role in activating the canonical NF-kB pathway and inhibiting TNF-a-induced cell death (12)(13)(14)(15). The role of LUBAC during development and function of B and T lymphocytes has also been dissected (16,(27)(28)(29)(30). In B cells, LUBAC plays crucial roles in TD and TI-II Ab responses by controlling CD40and TACI-mediated activation of the canonical NF-kB and ERK pathways, respectively; it also regulates B1 cell development (16).…”
Section: Discussionmentioning
confidence: 99%